Developing student personality in the context of the new european paradigm in Ukraine through teaching english language - Zemliakova, Olena (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article explores the importance of shaping the personality of students in Ukraine within the context of the new European paradigm. The authors discuss approaches to teaching English, including critical thinking, cultural diversity, and global perspective, aimed at preparing students for life in a global society.

Стаття розглядає важливість формування особистості студентів в Україні в новій європейській парадигмі. Автори обговорюють підходи до викладання англійської, зокрема критичне мислення, культурне розмаїття та глобальну перспективу, спрямовані на підготовку студентів до життя в глобальному суспільстві.
Keywords: personality development; new european paradigm; english language learning; critical thinking; global perspective